Effects of Zinc Magnesium Aspartate (ZMA) supplementation on training adaptations and markers of anabolism and catabolism - Wilborn, C. D.; Kerksick, C. M.; Campbell, B. I.; Taylor, L. W.; Marcello, B. M.; Rasmussen, C. J.; Greenwood, M. C.; Almada, A.; Kreider, R. B. (Journal of the International Society of Sports Nutrition, 2004)
This study examined whether supplementing the diet with a commercial supplement containing zinc magnesium aspartate (ZMA) during training affects zinc and magnesium status, anabolic and catabolic hormone profiles, and/or training adaptations. Forty-two resistance trained males (27±9 yrs; 178±8 cm, 85±15 kg, 18.6±6% body fat) were matched according to fat free mass and randomly assigned to ingest in a double blind manner either a dextrose placebo (P) or ZMA 30-60 minutes prior to going to sleep during 8-weeks of standardized resistance-training. Subjects completed testing sessions at 0, 4, and 8 weeks that included body composition assessment as determined by dual energy X-ray absorptiometry, 1-RM and muscular endurance tests on the bench and leg press, a Wingate anaerobic power test, and blood analysis to assess anabolic/catabolic status as well as markers of health. Data were analyzed using repeated measures ANOVA. Results indicated that ZMA supplementation non-significantly increased serum zinc levels by 11 - 17% (p=0.12). However, no significant differences were observed between groups in anabolic or catabolic hormone status, body composition, 1-RM bench press and leg press, upper or lower body muscular endurance, or cycling anaerobic capacity. Results indicate that ZMA supplementation during training does not appear to enhance training adaptations in resistance trained populations.